2015
DOI: 10.3109/00207454.2015.1036422
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genes modifying the age at onset in Huntington's disease in Uruguayan patients

Abstract: Huntington's disease (HD) is a hereditary neurodegenerative disorder. The genetic cause is an expansion of CAG repeats located in the IT15 gene. Though the number of CAG repeats ((CAG)n) can largely explain the age at onset (AAO) of symptoms, a percentage of its variation could be attributed to modifier genes and to environmental factors. The study aimed to evaluate the influence of genetic modifiers of the AAO of HD including: (CAG)n and del2642 in the IT15 gene, ADORA2A rs5751876, HAP1 rs4523977, PGC1-α rs76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…First, the number of inherited repeats typically positively correlates with disease severity and negatively correlates with age of onset. Diseases with strong correlations between the number of repeats and age of onset are SCA7 (16,17), SCA3 (18), SCA2 (19 -21), SCA37 (22), HD (23)(24)(25)(26), DM1 (27,28), dentatorubral-pallidoluysian atrophy (DRPLA) (29,30), X-linked dystonia parkinsonism (XDP) (31), familial adult myoclonic epilepsy 3 (FAME3) (32), and Friedreich's ataxia (FRDA) (33,34). For some disorders, the correlation between the number of repeats and symptom manifestation is less clear, although there typically is a marginally significant trend (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…First, the number of inherited repeats typically positively correlates with disease severity and negatively correlates with age of onset. Diseases with strong correlations between the number of repeats and age of onset are SCA7 (16,17), SCA3 (18), SCA2 (19 -21), SCA37 (22), HD (23)(24)(25)(26), DM1 (27,28), dentatorubral-pallidoluysian atrophy (DRPLA) (29,30), X-linked dystonia parkinsonism (XDP) (31), familial adult myoclonic epilepsy 3 (FAME3) (32), and Friedreich's ataxia (FRDA) (33,34). For some disorders, the correlation between the number of repeats and symptom manifestation is less clear, although there typically is a marginally significant trend (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…ADORA2B encodes adenosine receptor subtype A2B, a protein that interacts with netrin-1, which is involved in axon elongation. Currently, ADORA2B is not part of the HD pathway, although ADORA2A is ( 55 57 ). ADORA2A and ADORA2B are two of four human genes that encode adenosine receptors that increase cyclic adenosine monophosphate ( 58 ), which is important for signal transduction and other biochemical processes ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…100 The impact of ADORA2A genotype on residual variation was modest; however, these results have been replicated in two other studies. 101,102 One of the latter found that rs2298383 in intron 1 (in linkage disequilibrium with rs5751876) to be the most strongly associated ADORA2A variant. 101 These findings are supported by our knowledge of other environmental modifiers of HD (such as caffeine intake 103 ) and data from animal models on the roles of A 1 R and A 2A R. 104…”
Section: Neurologic and Neurodegenerative Disordersmentioning
confidence: 99%
“…100 The impact of ADORA2A genotype on residual variation was modest; however, these results have been replicated in two other studies. 101,102 One of the latter found that rs2298383 in intron 1 (in linkage disequilibrium with rs5751876) to be the most strongly associated ADORA2A variant. 101 These findings are supported by our knowledge of other environmental modifiers of HD (such as caffeine intake 103 ) and data from animal models on the roles of A 1 R and A 2A R. 104 Horgusluoglu-Moloch et al used the dataset from the Alzheimer's Disease Neuroimaging Initiative cohort and selected 1,563 non-Hispanic Caucasian participants to correlate different quantitative phenotypes (including hippocampal volume, metabolic activity, cerebrospinal fluid total tau level, amyloidosis in the hippocampus, and composite memory) with 18407 SNPs in 81 genes from a targeted neurogenesis pathway.…”
Section: Neurologic and Neurodegenerative Disordersmentioning
confidence: 99%